2021
DOI: 10.3390/molecules26123625
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial, Antioxidant, Anti-Acetylcholinesterase, Antidiabetic, and Pharmacokinetic Properties of Carum carvi L. and Coriandrum sativum L. Essential Oils Alone and in Combination

Abstract: Herbs and spices have been used since antiquity for their nutritional and health properties, as well as in traditional remedies for the prevention and treatment of many diseases. Therefore, this study aims to perform a chemical analysis of both essential oils (EOs) from the seeds of Carum carvi (C. carvi) and Coriandrum sativum (C. sativum) and evaluate their antioxidant, antimicrobial, anti-acetylcholinesterase, and antidiabetic activities alone and in combination. Results showed that the EOs mainly constitut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 67 publications
2
51
0
3
Order By: Relevance
“…Compared to acarbose with IC 50 of 14.60 µM against pancreatic α-amylase, the most abundant flavonoid in Co. sativum leaves as quercetin exhibited IC 50 of 12.7 µM [ 34 ], while the major phenolic acid, caffeic acid, exhibited IC 50 of 20.4 µM [ 38 ]. With high quercetin and caffeic acid contents that act as strong α-amylase inhibitors, Co. sativum is a good candidate as an anti-diabetic agent, even its seeds [ 39 , 40 , 41 ]. Likewise, P. tetragonolobus (or winged bean) is a Thai local vegetable normally consumed as boiled or blanched young bean pod with many spicy sauces.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to acarbose with IC 50 of 14.60 µM against pancreatic α-amylase, the most abundant flavonoid in Co. sativum leaves as quercetin exhibited IC 50 of 12.7 µM [ 34 ], while the major phenolic acid, caffeic acid, exhibited IC 50 of 20.4 µM [ 38 ]. With high quercetin and caffeic acid contents that act as strong α-amylase inhibitors, Co. sativum is a good candidate as an anti-diabetic agent, even its seeds [ 39 , 40 , 41 ]. Likewise, P. tetragonolobus (or winged bean) is a Thai local vegetable normally consumed as boiled or blanched young bean pod with many spicy sauces.…”
Section: Discussionmentioning
confidence: 99%
“… The role of C. sativum phytochemicals in some of its biological activities from different studies ① Suttisansanee, Thiyajai, Chalermchaiwat, Wongwathanarat, Pruesapan, Charoenkiatkul and Temviriyanukul [ 72 ], ② Kajal and Singh [ 73 ], ③ Hajlaoui, Arraouadi, Noumi, Aouadi, Adnan, Khan, Kadri and Snoussi [ 75 ], ④ Hajlaoui, Arraouadi, Noumi, Aouadi, Adnan, Khan, Kadri and Snoussi [ 75 ], ⑤ Cha, Yoon, Kim, Kim and Lee [ 76 ], and ⑥ Ramadan, et al [ 77 ]. …”
Section: Figurementioning
confidence: 99%
“…From the above-mentioned study, it was found that linalool in addition to other terpenes and fatty acids has the potential to bind with the RAGE receptor and subsequently block AGEs’ damaging action. In a different study, the Eos’ major components of C. sativum were linalool, γ-terpinene, and α-pinene with prominent activities against diabetes, microbial infections, and acetylcholinesterase enzyme [ 75 ]. Other activities such as hypotensive [ 20 ] and neuroprotective ones [ 76 ] were detected in flavonoids- and isocoumarin glycosides-containing fractions of C. sativum, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…According to the results, M. ferrea flower extract showed high total phenolic content. The previous study has been reported that the ethanolic M. ferrea flower extract contained phenolic compounds, eugenol and cinnamaldehyde, as the major compounds [48]. These compounds have anti-inflammatory effects induced by C. acnes [49,50].…”
Section: Anti-inflammatory Activitiesmentioning
confidence: 91%